Taxonomic revision of the aequata-group of the subgenus Eucera s. str (Hymenoptera, Apidae, Eucerini) - Dorchin, Achik (Zootaxa, 2019)
The aequata-group of the subgenus Eucera s. str. Scopoli from the Eastern Mediterranean region, Bulgaria, and Iran is described, and the three species included are revised. The little-known E. aequata Vachal 1907 known from Turkey, Cyprus, Syria and Israel, is redescribed and a Lectotype is designated. Two species are described as new: E. dafnii sp. nov. from Iran, Israel, Syria, Turkey, Bulgaria, and Greece, and E. wattsi sp. nov. from Israel and Lebanon. An identification key is provided, and natural history information including assessment of preferred pollen host plants is presented.